The Influence of Interactive Learning Media on Students Interest in Learning in Mathematics Subjects at UPTD SMPN 7 Sinjai - Mirnawati; Takdir; Irmayanti (JTMT: Journal Tadris Matematika, 2024)
This study aims to determine whether interactive learning media has an effect on students' interest in learning mathematics at UPTD SMP Negeri 7 Sinjai. The type of research used in the study is Ex Post Facto with a quantitative approach. The population in this study were all students of class VIII at UPTD SMPN 7 Sinjai totaling 128 students and the sample in this study was 56 students. Data collection techniques were through questionnaires and documentation. Data analysis techniques in this study used descriptive statistics and inferential statistics. The results of the study based on hypothesis testing with simple linear regression and t-test obtained a coefficient value with a significance value of 0.00001 <0.05 and a t-count value of 4.655 and a value for t-table of 1.672 so the t-count value> t-table or 4.655> 1.672, with an R Square value of 28.6%. So H0 is rejected and Ha is accepted, so this proves that there is an influence of interactive learning media on students' interest in learning mathematics at UPTD SMPN 7 Sinjai.